Divalent cations are antagonistic to survivability of freeze-dried probiotics encapsulated in cross-linked alginate - Tan, Li Ling (2020)
Alginate encapsulation is amongst the most studied probiotic encapsulation formulations in the literature, preferred for its low toxicity, low cost and ability to protect entrapped probiotics against acidic pH. Despite extensive academic studies, there has been little commercial translation of alginate-encapsulated probiotic formulations. In this study, we hypothesized that factors affecting freeze-drying survivability of alginate-encapsulated probiotics could have limited its translation potential. Factors including: 1) encapsulant material, 2) cryoprotectant, 3) cross-linker, 4) Concentration of crosslinker, and 5) other Group II divalent cations cross-linkers were investigated, using two model probiotics – Lactobacillus rhamnosus GG (LGG) and Escherichia coli Nissle 1917 (ECN). Divalent cations, which are used to cross-link alginates, were found to have antagonistic effects on the freeze-drying survivability of LGG and ECN. To mitigate the deleterious effects of divalent cations, the addition of sucrose was found to be useful, possibly due to its membrane stabilization mechanism.